Zoomout HELLO: A novel 1-hop broadcast scheme to improve network QoS for VANET on highways - Rehan, M. (Springer Verlag, 2015)
On highways, each vehicle uses periodic 1-hop broadcast messages to advertise its position and other information so that vehicles in the vicinity and those which are hops away can find the advertising vehicle for information exchange. During destination discovery, a vehicle issues broadcast messages, which travel hop by hop in search of destination. We argue that since periodic 1-hop messages are sent on regular intervals, so these can be manipulated in such an intelligent way that routing protocols may not need to execute broadcast destination discovery procedure. The continuous periodic HELLO broadcast mechanism can assist the routing protocol in this regard. The proposed ZoomOut HELLO (ZOH) technique introduces a neighbour-cum-forwarding (NF) table. In this scheme, periodic ZOH mechanism will populate the NF table, while the forwarding mechanism will use it. We introduce the concepts of Front and Behind relatives, which are selected out of 1-hop neighbours based on the typed HELLO messages exchanged between 1-hop neighbours. ZOH is a broadcast suppression technique and implicitly provides chain of relatives in the front and behind direction of each vehicle. A routing protocol can therefore use this chain. We have developed analytical model for ad-hoc on-demand distance vector (AODV), preferred group broadcast (PGB), reliable opportunistic broadcast (R-OB-VAN) and ZoomOut HELLO, and implemented them in MATLAB. The results show that ZoomOut HELLO generates least number of RREQ rebroadcast messages and has minimum network delay due to RREQ messages. Â© Springer Science+Business Media Singapore 2015.